Social Work Tratment Interlocking Theoretical Appraches - Turner, Francis J. (Francis Joseph) (New York oxford University Press, 2011)
"First published in 1974, Social Work Treatment remains the most popular and trusted compendium of theories available to social work students and practitioners. With contributions from leading professionals and researchers, it explores the full range of
Keywords: Social service. Social Work -- methods. Psychological Theory